STRATEGI PENDIDIKAN KONTEMPORER DALAM MENGEMBANGKAN KOGNITIF ANAK USIA DINI: SYSTEMATIC LITERATURE REVIEW - Elya Nora; Farida Mayar; Humairah; Windi Elsa Putri; Wiwit April Mardiyanti; Zahra Tsabita Putri (STKIP Subang, 2025)
This study aims to identify and analyze contemporary educational strategies that are effective in developing cognitive abilities in early childhood through a Systematic Literature Review (SLR) approach. The SLR method was carried out by selecting articles published between 2015 and 2025 from various databases from Google Scholar, Scopus, ScienceDirect, and SpringerLink. using the keywords